Design Of An Intranet Network System For Data Collection Of Student Offenses / High School 1 Hamparan Perak Using Website Technology - Aldika, Iqbal; Andhika Putri, Nadya; Amin, Muhammad (Cattleya Darmaya Fortuna, 2025)
The increasing need for efficient data management in educational institutions has highlighted the limitations of traditional methods in documenting student offenses. This study focuses on designing an intranet network system for High School 1 Hamparan Perak to streamline the data collection of student offenses using website technology. The proposed system aims to replace manual record-keeping with a centralized, digital platform that enhances data accuracy, accessibility, and security. By leveraging an intranet-based approach, the system ensures that authorized personnel can input, update, and access data in real-time, facilitating better monitoring and analysis of student behavior trends. This study outlines the system's architecture, the benefits of integrating website technology into school operations, and its potential to improve communication among staff members regarding student discipline. The findings suggest that implementing this intranet network system will lead to more organized and responsive management of student offenses, contributing to a more disciplined educational environment.